Molecular phylogenetics and conservation aspects of antelopes - Rebholz, Wilhelmus Ewald Reinaard (Division of Chemical Pathology, 2018)
This thesis concerns the molecular phylogenetics of three tribes of the family Bovidae, the Antilopini, Neotragini, and Tragelaphini. None of these tribes have been studied extensively with molecular techniques. The tribe Antilopini is one of the most speciose tribes (it includes 6 genera with 20 species) and the classification of several species of the genus Gazella is not clear. The tribe Neotragini is thought to be paraphyletic. Mitochondrial sequences of the cytochrome c oxidase ill and cytochrome b genes totalling 1083 base pairs have been determined for 52 taxa and used to determine phylogenetic relationships using cladistic and distance methods. Karyological analysis identified polymorphisms in several species (especially in Gazella saudiya and G. subgutturosa). Karyotypes of G. dorcas pelzelni and an XXY karyotype of a G. dorcas individual are shown for the first time. The main conclusions are that the Antilopini and the Tragelaphini are monophyletic and that the tribe Neotragini is paraphyletic. There is a lack of phylogenetic resolution between tribes which is probably due to the rapid radiation of the different tribes about 20 million years ago. The genus Taurotragus in the tribe Tragelaphini is shown to be paraphyletic and it would be appropriate to incorporate these taxa in the genus Tragelaphus. The genus Gazella could be paraphyletic, due to the position of Antilope cervicapra, in which case the genus needs to be split into two genera or renamed as Antilope. It is also argued that the use of the subgenus Trachelocele should be discontinued and that its only species, G. subgutturosa should be included in the subgenus Gazella. G. rufifrons and G. thomsonii may be more appropriately considered as conspecific. Cytogenetic and sequence data reveal that the herd of G. saudiya in Al Areen Wildlife Park is hybridised with G. bennettii and it is argued that it is important to identify unhybridised G. saudiya in other collections, since this species is on the brink of extinction. This case study demonstrates the need to genetically screen individuals which are part of a captive breeding program, especially if they are intended for reintroduction into the wild.